2018
DOI: 10.1128/mbio.02158-17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Function and Competitive Inhibition of Pseudomonas aeruginosa Multiple Virulence Factor Regulator

Abstract: New approaches to antimicrobial drug discovery are urgently needed to combat intractable infections caused by multidrug-resistant (MDR) bacteria. Multiple virulence factor regulator (MvfR or PqsR), a Pseudomonas aeruginosa quorum sensing transcription factor, regulates functions important in both acute and persistent infections. Recently identified non-ligand-based benzamine-benzimidazole (BB) inhibitors of MvfR suppress both acute and persistent P. aeruginosa infections in mice without perturbing bacterial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 42 publications
1
73
1
Order By: Relevance
“…The results of this investigation indicated that although Q194E retained at least 88% functionality, this mutant was virtually inactive and almost failed to respond to the Pseudomonas quinolone signal in the pqsA mutant. On the other hand, a hydrophobic amino acid at position 258 is required for PqsR functionality since Y258A mutation renders PqsR inactive (35). No mutations at positions 194 and 258 were seen in our study, but the only missense mutation in the present study (A314V) increased protein stability along with having a neutral impact on protein function.…”
Section: Discussioncontrasting
confidence: 46%
“…The results of this investigation indicated that although Q194E retained at least 88% functionality, this mutant was virtually inactive and almost failed to respond to the Pseudomonas quinolone signal in the pqsA mutant. On the other hand, a hydrophobic amino acid at position 258 is required for PqsR functionality since Y258A mutation renders PqsR inactive (35). No mutations at positions 194 and 258 were seen in our study, but the only missense mutation in the present study (A314V) increased protein stability along with having a neutral impact on protein function.…”
Section: Discussioncontrasting
confidence: 46%
“…At present, the QS system (Figure 3) is more deeply understood in P. aeruginosa , which harbors four types of QS systems, including two LuxI/LuxR‐type (LasI/LasR and RhlI/RhlR) systems, a pseudomonas quinolone signal (PQS) system, and an integrating quorum sensing signal (IQS) system, all of which influence almost 10% of gene expression in P. aeruginosa , constituting a hierarchical regulatory network (Shrikant & Chandrajit, 2018). These four types of systems synthesize N‐3‐oxododecanyol‐L‐homoserine lactone (3OC12HSL), N‐butanoyl‐L‐homoserine lactone (C4‐HSL), 2‐heptyl‐3‐hydroxy‐4‐quinolone (PQS), and IQS as respective signal molecules to form complexes with corresponding receptors, and then activate genes encoding virulence factors such as elastase, proteases, rhamnolipids, hemolysins, toxins, pyocyanin, and alginate, which usually damage tissues and organs and interfere with the defense mechanisms of the human immune system, triggering different types of infection (Guo et al., 2014; Kitao et al., 2018). Moreover, swarming motility and biofilm formation are also under the control of QS system in P. aeruginosa (Rutherford & Bassler, 2012).…”
Section: Bacterial Toxinsmentioning
confidence: 99%
“…PqsR (MvfR) is a key component of alkyl-quinolone-dependent QS in P. aeruginosa [13]. The LBD of PqsR consists of two subdomains connected by an antiparallel β-sheet hinge region, with a large ligand binding pocket in which a native agonist 2-nonyl-4-quinolone (NHQ) is stabilized entirely by hydrophobic interactions [13,14]. Residues Leu189, Leu207, Leu208, Ala168, Ile149, Ile236, Tyr258, Ile186 and Val170 take part in the above hydrophobic interactions between PqsR and NHQ.…”
Section: Introductionmentioning
confidence: 99%